Performance analysis of a thermally regenerative electrochemical refrigerator. (1st October 2016) - Li, Baode; Long, Rui; Liu, Zhichun; Liu, Wei
Abstract: Performance analysis and optimization of a thermally regenerative electrochemical refrigerator (TRER) are investigated based on finite time analysis. The general expressions of some important parameters of TRER are derived. The χ figure of merit considers both the coefficient of performance (COP) and cooling load rate, which can be seen as a compromise between maximum cooling load rate and maximum COP. Based on this, the traditional region between both can be divided into two more specific performance regions that represent two different operating demands. Under the maximum χ figure of merit, the impacts of the cell material's characteristics, heat conductance of heat exchangers, and heat reservoir temperature ratio on the corresponding cooling load rate and COP are analyzed in detail. Results reveal that materials with larger isothermal coefficient, specific charging/discharging capacity, lower internal resistance, and specific heat correspond to higher cooling load rate and extracted COP. Better heat exchange performance of the regenerator increases cooling load rate and power input; however, it does not guarantee a higher corresponding COP. We expect this work to contribute to designing and operating high performance TRER devices. Highlights: An analysis of the TRER is conducted under the χ criterion. The optimal operating regions of the TRER have been proposed. Parameters' impacts on performance of the TRER have been analyzed. Higher performance of heat exchangers does not guarantee higher COP.